Friendship versus love in Ibsen's dramas - Wicklund, Beret (Nordlit, 2015)
The article explores how friendships between men and women are presented in the dramas A Doll’s House, The Lady from the Sea, Rosmersholm and Hedda Gabler. Friendship is an important motive which functions to show women’s subordinate role in the bourgeois society in Ibsen’s time. Friendship seems to be a positive alternative relation to love and marriage for women, as it has the element of equality and freedom from traditional female roles. When love is declared, though, this hope is destroyed and it is revealed how all relations are involved in patriarchy and finances. Friendships also function for both male and female characters as an illusion and a convenient psychological cover for unpleasant feelings of guilt the characters are not able to admit or express. This functions in presenting the different cultural standards for men and women as it pertains to what are socially accepted of sexual feelings and experiences. In this way, we see how Ibsen, through his dramas, takes part in the important cultural debate on sexuality in Norway in his time, reflecting different arguments in this debate.
Keywords: Ibsen; feminism; love; relationships; friendship; sexuality.